Draft Ninth Five Year Plan (1997-2002) and Annual Plan, 1997-98 Vol. I General Profile and Sectoral Reviews Government of Uttar Pradesh - Planning Commission (Planning Commission, 1997)
Uttar Pradesh is the most populous state, with its highest share of 16.4 percent in country’s population. It is also the fourth largest state in geographical area, encompassing 2.94 lakh square kms. and comprising 83 districts, 901 Development blocks and 112804 populated villages. The geographical area of the state is 9.0 percent of the country’s area. A lower share in country’s area with higher share in its population has led to a higher density of population in the state compared with most states and the country, as a whole. The density in die state was 473 person per square kms. in 1991 against 274 for the country.
Government of Uttar Pradesh, State Planning Commission